Piodalan Sebuah Prosesi Memupuk Seni dan Komunikasi : (Studi Kasus di Pura Batur Sari Tabanan) - Paramita, Santhi Pradnya (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Batur Sari Temple, which is in the Banjar Gerokgak Tengah, Tabanan, is a temple that is carried on by the Kawula Batur Sari extended family. The Piodalan of Batur Sari Temple is commemorated by every Budha Umanis Prangbakat. As one of the religious ceremonies, the Piodalan of Batur Sari Temple is certainly full of artistic and cultural activities. Art, especially Balinese dance when the piodalan takes place, occurs spontaneously. There is no special preparation for it. So, through this community service, it is hoped that existing artistic activities can be further fostered by presenting special training activities ahead of piodalan. This is done of course to be able to increase the intensity of artistic activities. This activity also eventually became tit for tat related to improving communication, especially among young women. Through training and demonstration methods, three Balinese dance materials were finally filled, namely the pendet pamendak dance, the rejang renteng dance, and the rejang sari dance. All the dancers seemed enthusiastic about giving the dance offerings. They dance with sincerity as an essence of the implementation of yadnya. The piodalan moment has finally automatically fostered artistic and communication activities in Kawula Batur Sari.